2011
DOI: 10.1007/s00038-011-0236-x
|View full text |Cite
|
Sign up to set email alerts
|

Time series analysis of Japanese encephalitis and weather in Linyi City, China

Abstract: Weather variables might be treated as possible predictors of Japanese encephalitis incidence for regions with similar geographic, weather, and socio-economic conditions to Linyi, China.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
29
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 44 publications
3
29
0
Order By: Relevance
“…Especially given that global temperature has been generally warming, more attention has been paid to the relationship of infectious diseases with meteorological factors. Some studies were found to report the relationship between them (Lin et al 2012;Soebiyanto et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Especially given that global temperature has been generally warming, more attention has been paid to the relationship of infectious diseases with meteorological factors. Some studies were found to report the relationship between them (Lin et al 2012;Soebiyanto et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In [11], it was demonstrated that at the provincial level, the risk of JE seemed to be governed by high proportions of rice-planting area, rural population and the extent of pig rearing. The authors of [13,14,15] studied the impact of the climate variability on the transmission of JE. These studies give evidence on the association between JE cases and the contextual risk factors, including agricultural and climatic factors.…”
Section: Introductionmentioning
confidence: 99%
“…A detailed summary of the included studies is presented in (TABLE 1) Additional papers identified through other sources (n = 25) Vaccination [46] Monthly relative humidity Spatial lag term, The percentage of irrigated land, the percentage of grassland cover, pigto-human ratio [50] Mean monthly total precipitation (April)…”
Section: Methodsmentioning
confidence: 99%
“…Seven studies reported a positive association between temperature and JE incidence [44][45][46][47][48][49][50], and seven studies reported a positive association between precipitation and JE incidence [44,[46][47][48][49][50][51]. Three studies [45,46,48] suggested a positive association between relative humidity and JE incidence. Southern Oscillation Index (lag-6 months) was investigated by only one study, where a positive association with JE cases was reported [44].…”
Section: Hepatitis Bmentioning
confidence: 97%
See 1 more Smart Citation